The Optimization of Legal Protection of Costums Intellectual Property Traditional Cultural Expressions of Malay Customs - Nadirah, Ida; Medaline, Onny; Sahari, Alpi; Koto, Ismail (JURNAL AKTA, 2023)
This research aims to discuss Costums Intellectual Property in the field of Traditional Cultural Expression of Malay Customs which has promising economic potential in the field of tourism, both domestic tourism and foreign tourism potential. But until now it has not been protected optimally. This can be seen every year when the Malaysian Visit year will be displayed in many brochures promoting their tourist visits, traditional cultural expressions belonging to the indigenous Malay Peoples of Indonesia The purpose of this study is to analyze how many inventories and registrations of Costums Intellectual Property of Traditional Cultural Expressions of Malay Customs have been protected in the Regional Office of North Sumatra. The approach used in this study is a normative and empirical approach, namely through the review of laws and regulations related to the Protection of Costums Intellectual Property (KIK), especially related to Traditional Cultural Expressions of the Malay Indigenous Peoples of North Sumatra and conducting direct interviews with the head of the Intellectual Property Registration division of the North Sumatra KUMHAM Regional Office. The results showed that the level of awareness of indigenous peoples and local governments to protect their Costums Intellectual Property specifically in the field of traditional Malay Customary Cultural Expressions was very low, as seen from the data of the last three years, the inventory and registration of traditional Cultural Expressions of Malay indigenous peoples only amounted to twelve types of traditional culture.